Electrowetting actuated liquid prism with large steering angle based on additional gravitational effects. Issue 7 (22nd May 2018) - Luo, Lin; Li, Lei; Wang, Jin‐Hui; Yuan, Rong‐Ying; Wang, Qiong‐Hua
Abstract: In this paper, we propose a liquid prism based on electrowetting‐on‐dielectric and gravity effect. The device is filled with two immiscible liquids. The conductive liquid is filled in the upper part of the device, and the oil is filled in the bottom of the device. Different from the conventional liquid prism, the density of the conductive liquid is larger than that of the oil. The liquid–liquid interface can form a tilt shape when applied different voltages to the opposite sidewalls. The beam will be deflected when the light passes through the device. Our results show that the tilt angle of the liquid–liquid interface is 45°, and the light beam can be deflected by 22.2° (−10.9° to +11.3°). The actuation time of the device is 240 ms. The proposed liquid prism for light beam steering and tracking has potential application in laser directions, telecommunications, and scanners. Abstract : In this paper, we propose a liquid prism based on electrowetting‐on‐dielectric and gravity effect. The device is filled with two immiscible liquids. The liquid–liquid interface can form a tilt shape when applied different voltages to the opposite sidewalls. The beam will be deflected when the light passes through the device. Our results show that the tilt angle of the liquid–liquid interface is 45°, and the light beam can be deflected by 22.2° (−10.9° to +11.3°). The actuation time of the device is 240 ms. The proposed liquid prism for light beam steering and tracking has potential application in laser directions, telecommunications, and scanners.